Could the pandemic reshape world order, American security, and national defense? (2020)
The COVID-19 pandemic seems at once to be top of mind for international relations scholars while low on their list of enduring drivers. As economists and public health experts tally the virus’s accumulating effects, prominent international relations scholars have generally limited their analysis to the ways in which COVID-19 is accelerating trends already underway. Structural explanations prevail. The US national security community appears more concerned but conflicted. Will the pandemic convince Americans to draw inward, amplifying nationalist sentiments and reducing the appetite for multilateral approaches? Or will it give new impetus for global engagement? Making predictions in the middle of the pandemic is fraught. Yet history and recent events provide guides, and they point toward this pandemic mattering and mattering big. It will not only accelerate changes underway, but if policy makers are up for the challenge, it presents an opportunity to reshape the future of world order and national security. For defense watchers, this prospect is both daunting and fortuitous. The US defense world could use some reshaping if it is to contribute effectively to the nation’s future.